Transforming zakat distribution: Integrating Nahdlatul Ulama's fatwa to address Indonesia's social inequality challenges - Ahyani, Hisam; Solehudin, Ending; Mutmainah, Naeli; Rahman, Encep Taufik; Ahmad, Md Yazid; Muharir, Muharir; Sartono, Sartono; Fahmi, Ahmad Zulfi; Bhatti , Muhammad Safdar (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study explores the transformation of zakat distribution principles as outlined in Nahdlatul Ulama’s Fatwa Bahtsul Masail and its implications for Indonesia's legal regulations. The goal is to understand how these principles can enhance zakat management by addressing social inequality and poverty alleviation.Methodology – A normative juridical approach was used, with a descriptive analytical study based on a literature review. The research focuses on four main aspects: analyzing zakat distribution principles in the context of Indonesian law, examining the legal reasoning (istinbath hukum) behind these principles, identifying factors driving and hindering the transformation, and assessing the significance of implementing these principles in Indonesian legal frameworks.Findings – This study identifies three main principles—justice, equality, and regionality—that should be integrated into regulatory frameworks. It also highlights challenges, including a lack of public participation in zakat distribution through official institutions, such as NU CARE-LAZISNU.Implications – The findings suggest the need for increased socialization of zakat management principles by the National Amil Zakat Agency (Badan Amil Zakat Nasional, BAZNAS), based on both Sharia and secure legal regulations, to enhance the effectiveness of zakat management in Indonesia.Originality – This research provides valuable insights into the evolving principles of zakat distribution and their integration into legal frameworks, contributing to the adaptation of zakat management practices to contemporary challenges in Indonesia.